Réalisation d'un diagnostic territorial de développement durable. Expérimentation dans le Bassin potassique alsacien - François Besancenot (Développement Durable et Territoires)
Although several methodological helps for the local Agenda 21, many local governments have still difficulties to plan the sustainable development for their territory. Which territorial scale, which sustainable development aims, which evaluation to apply ? To reply, this article introduces the essential stages of a sustainable development diagnosis which can adjust to any territory. The theory has been confronted to the ground reality thanks to an example of regeneration territory considered as pertinent for a sustainable development plan: the Alsace potassium Basin.